Способ обращения с отработавшим ядерным топливом реактора РБМК-1000 и устройства для его осуществления - Гаврилов П. М. Петр Михайлович; Кравченко В. А. Вадим Альбертович; Гамза Ю. В. Юрий Вячеславович; Бараков Б. Н. Борис Николаевич; Ильиных Ю. С. Юрий Сергеевич; Шафрова Н. П. Наталия Павловна; Онуфриенко С. В. Сергей Викторович; Костюков В. Е. Валентин Ефимович; Долбищев С. Ф. Сергей Фёдорович
опубл. 27.08.13